ANALISIS PENERIMAAN DAN PENGGUNAAN DANA NON HALAL BERDASARKAN PSAK 109 PADA BANK SYARIAH INDONESIA - Nurjayani, Dwi; Harsanto, Molbi Febrio; Hanif, Hernawan (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
This study aims to analyze the compliance of the recognition and utilization of non-halal funds in the financial statements of Bank Syariah Indonesia with the Statement of Financial Accounting Standards 109 (PSAK 109). Non-halal funds refer to income derived from activities that do not align with sharia principles, such as interest from conventional banks or service fees from giro accounts. The method used is descriptive qualitative, with an observational approach to Bank Syariah Indonesia’s financial statements for the period 2020–2024. The findings indicate that the recognition, presentation, and disclosure of non-halal funds in the financial statements are generally in accordance with PSAK 109. However, the reporting of non-halal funds has not yet been presented in a separate and detailed manner. This suggests a need for improved transparency and accountability in financial reporting, particularly regarding the sources and uses of non-halal funds, to ensure full compliance with sharia accounting standards